'Distribution of Hepatitis C Virus genotypes in northern Greece in the last decade: descriptive analysis and clinical correlations'. (2019) - Gioula, G.; Sinakos, E.; Gigi, E.; Goulis, I.; Vasiliadis, T.; Minti, F.; Akriviadis, E.
Abstract: Hepatitis C virus (HCV) represents a major public health problem, while the identification of a HCV genotype is clinically very important for therapy prescription. The aim of the present study was to determine the HCV genotype distribution patients from northern Greece with HCV RNA positive viral load and to identify whether there is a shift in this distribution, during 2009–2017. The study was performed on 915 HCV positive patients and according to the results, genotype 3 was the most prevalent genotype ( Ν = 395, 43.2%) followed by genotype 1 ( Ν = 361, 39.5%). Regarding the gender of the patients, genotype 1 was mostly detected in women. Moreover, genotype 1 was associated with higher viral loads, while genotype 3 was most frequently detected in patients with a history of intravenous drug use. In conclusion, our results show that genotype 3 is the most prevalent genotype in Greece during the last decade as opposed to older epidemiological studies, likely due to intravenous drug use becoming the major source of infection.